Compositional Effects of Large Graphene Oxide Sheets on the Spinnability and Properties of Polyurethane Composite Fibers. Issue 5 (11th January 2016) - Seyedin, Shayan; Razal, Joselito M.; Innis, Peter C.; Jalili, Rouhollah; Wallace, Gordon G.
Abstract : Recent advances in wearable electronics, technical textiles, and wearable strain sensing devices have resulted in extensive research on stretchable electrically conductive fibers. Addressing these areas require the development of efficient fiber processing methodologies that do not compromise the mechanical properties of the polymer (typically an elastomer) when nanomaterials are added as conductive fillers. It is highly desirable that the addition of conductive fillers provides not only electrical conductivity, but that these fillers also enhance the stiffness, strength, stretchability, and toughness of the polymer. Here, the compatibility of polyurethane (PU) and graphene oxide (GO) is utilized for the study of the properties of elastomeric conductive fibers prepared by wet‐spinning. The GO‐reinforced PU fibers demonstrate outstanding mechanical properties with a 200‐fold and a threefold enhancement in Young's modulus and toughness, respectively. Postspinning thermal annealing of the fibers results in electrically conductive fibers with a low percolation threshold (≈0.37 wt% GO). An investigation into optimized fiber's electromechanical behavior reveals linear strain sensing abilities up to 70%. Results presented here provide practical insights on how to simultaneously maintain or improve electrical, mechanical, and electromechanical properties in conductive elastomer fibers. Abstract : Polyurethane/graphene oxide composite fibers, which are electrically conducting, mechanically stiff, strong, and tough, are fabricated using a facile wet‐spinning technique. The composite fibers demonstrate strain sensing properties with a reproducible response over a wide range of applied strains.